(untitled) (Journal of the College of Basic Education, 2023)
Susan Glaspell (1876-1948) was one of the pioneering American female playwrights who evolved into visibility at the end of the 19th century and the beginning of the twentieth. She had celebrated in her personal and literary life the advent of the new woman striving to fulfill her dreams in a hostile and intensive world. Glaspell based her first dramatic play, Trifles, on an actual murder case she covered while working as a journalist.1 She may write her piece, Trifles, as an explanation for why a woman may murder her husband. In her attempt to explain, Glaspell created the character of Minnie Wright who is oppressed by her husband to the extreme. To fully free herself, Minnie escapes by way of strangling her husband to death. Thematically speaking, Glaspell’s Trifles handles women’s issues in a time where women like Minnie Wright were often forced to remain with “either father or husband just to have a roof over their heads. The life of a solitary woman without male protection was not an attractive option.”2 In Trifles, the troubled marriage of the Wrights has culminated in Minnie Wright strangling her husband, John. The men vainly look for signs of violent rage, but the women, with growing empathy, are able to recognize the signs of quiet desperation under which many women of their time were forced to live. Glaspell contrasts male and female perspectives throughout the play, and engages the audiences’ sympathy firmly on the side of the women. Susan C. W. Abbotson indicates that “We are asked to witness Mrs. Wright’s life rather than Mr. Wright’s death, and we are shown that the true ‘crime’ has been the way she was being subjugated and ‘destroyed’ by her marriage.”3 Mr. Wright sees women as a submissive group whose concerns hold